2015
DOI: 10.1093/hmg/ddv207
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting cytosolic translation and autophagy improves health in mitochondrial disease

Abstract: Mitochondrial respiratory chain (RC) disease therapies directed at intra-mitochondrial pathology are largely ineffective. Recognizing that RC dysfunction invokes pronounced extra-mitochondrial transcriptional adaptations, particularly involving dysregulated translation, we hypothesized that translational dysregulation is itself contributing to the pathophysiology of RC disease. Here, we investigated the activities, and effects from direct inhibition, of a central translational regulator (mTORC1) and its downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 53 publications
4
71
0
Order By: Relevance
“…Of these lithium is known to be an inhibitor of mitophagy [64]. Lysosomal inhibitors also slow autophagy and mitophagy, the antimalarial drug, chloroquine, being a well-known example that prevents lysosomal acidification and proteolysis [65].…”
Section: Chemicalmentioning
confidence: 99%
“…Of these lithium is known to be an inhibitor of mitophagy [64]. Lysosomal inhibitors also slow autophagy and mitophagy, the antimalarial drug, chloroquine, being a well-known example that prevents lysosomal acidification and proteolysis [65].…”
Section: Chemicalmentioning
confidence: 99%
“…However, RC disease also results in deficiencies of NAD + and uridine, as well as excessive free radical production. In particular, a relative increase in the ratio of reduced NAD + (NADH) to NAD + [103], as well as absolute deficiencies of both of these essential redox metabolites [104], alters flux through hundreds of downstream metabolic pathways, including amino acid metabolism [97]. Targeted blood metabolite analyses in 19 patients with RC disease identified that they have an almost two-fold increase in the ratio of several amino acids when normalized to glutamate as compared to healthy individuals [105].…”
Section: New Technologies and “Omic” Approaches To Diagnosis Treamentioning
confidence: 99%
“…This highly conserved signaling network functions to collectively sense the cellular nutrient and health status to enable cells to make the ultimate decision to either grow or die, where these essential activities are coordinated by the signaling network to mediate the specific response of hundreds of downstream biological processes and biochemical pathways [99]. For example, RC inhibition alters the expression and ability of glucose to inhibit FOX01 [100], activates AMPK and mTORC1 [104] and inhibits PPAR family gene activity in different tissues, key signaling and regulatory pathways for cellular function [100]. Many of these signaling changes can be reversed by treating cells with glucose [104] as well as by a range of drugs that target their specific activities [104, 106].…”
Section: New Technologies and “Omic” Approaches To Diagnosis Treamentioning
confidence: 99%
See 2 more Smart Citations